Primitive Weevils of Florida (Insecta: Coleoptera: Brentidae: Brentinae) - Michael C. Thomas (EDIS, 2007)
EENY-400, a 4-page illustrated fact sheet by Michael C. Thomas is part of the Featured Creatures collection. It describes this relatively small, primarily tropical group of weevils in the subfamily Brentinae, discussing their identification and selected references. Published by the UF Department of Entomology and Nematology, September 2007.